Proportions, five-year survival rates of hypopharyngeal cancer and its associated factors among head and neck cancer patients at a tertiary care hospital in Northern Tanzania - Fakhi, Mariam; Mtenga, Philbert; Serventi, Furaha; Chussi, Desderius C.; Kimaro, Innocent S.; Msuakollo, Asnah S.; Samsoni, Fadhili (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Hypopharyngeal cancer is a rare, aggressive form of cancer of the hypopharynx. It is one of the public health problems with a high burden in low and middle-income countries (LMICs). Despite the advancement in cancer management, mortality associated with cancer continues to rise mostly in LMICs like Tanzania. Yet, the contribution of hypopharyngeal cancer to the observed outcome is not known. Methods: A hospital based cohort study was conducted at a tertiary care hospital in northern Tanzania, Kilimanjaro Christian Medical Center (KCMC), from January 2015 to December 2019. Kaplan-Meier estimates were used to determine the survival rate. Cox regression analysis assessed factors associated with survival status. A p value <0.05 was considered statistically significant. Results: A total of 1,259 participants with head and neck cancer were included in this study. Among them, 97 (7.7%) had hypopharyngeal cancer. Participants with hypopharyngeal cancer were followed for five years. The median survival time was 32.0 months at the end of follow-up, and 45 (46.4%) participants had died. Participants with stage IV cancer had a 3.82 times higher hazard of mortality compared to those with stage II. Additionally, those with distant metastasis had a 9.90 times higher hazard of death. Conclusions: The study reported a poor survival rate with a five-year mortality rate of 46.4%. Participants with cancer at stage IV, and those with the presence of distant metastasis, had a higher hazard of mortality compared to their counterparts.